PENDIDIKAN ANAK USIA DINI DI DKI JAKARTA - Rugaiyah Rugaiyah (Jurnal Ilmiah Visi, 2011)
Early childhood education is a foundation for further education of the children and the parents, societies, and the government should pay serious attention to the implementation of early childhood education program in Jakarta focusing on academic qualification, motivation, competence, and self development of early childhood education teachers. As a survey, this research employed explorative and descriptive methods and collected data using interview and document study techniques. The conclusion of this research shows (a) most of the teachers have undergraduate certificates, (b) the teachers are motivated by internal and external factors, (c) most of the teachers have professional competence, more than a half of them have pedagogic competence, less than a half of them have social competence, and almost all of them have good or excellent character competence, (d) self development is done through the training offered by the institution or by their own and efforts.